2020
DOI: 10.2478/sg-2020-0006
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of growth characteristics and wood properties for solid wood production from Eucalyptus camaldulensis half-sib families growing in Thailand

Abstract: To promote solid wood production, the diameter at breast height, height, stress-wave velocity, surface-released strain, basic density and compressive strength parallel to the grain were measured for 10 half-sib families of 12-year-old Eucalyptus camaldulensis Dehnh. trees growing in Thailand. Based on the results, growth rates, correlations among measured properties, radial and among-family variations of wood properties, and their repeatability were evaluated. Diameter at breast height, height, and wood volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…In these studies, wood properties became stable below the age of 10 years at the time of peak CAI and MAI values in L. tulipifera in Japan (Fig. 1), Populus × beijingensis in China [9], and E. camaldulensis in Thailand [14], suggesting that xylem maturation occurs in accordance with a decrease in the radial growth rate in these species. Wireman and Williamson [30] showed that the radial increase in basic density was associated with a shift in the allocation of resources from growth with the production of low-specific gravity wood to greater structural reinforcement of the trunk (production of denser wood) in three tropical pioneer species (Hampea appendiculata, Heliocarpus appendiculatus, and Ochroma pyramidale) in Costa Rica.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…In these studies, wood properties became stable below the age of 10 years at the time of peak CAI and MAI values in L. tulipifera in Japan (Fig. 1), Populus × beijingensis in China [9], and E. camaldulensis in Thailand [14], suggesting that xylem maturation occurs in accordance with a decrease in the radial growth rate in these species. Wireman and Williamson [30] showed that the radial increase in basic density was associated with a shift in the allocation of resources from growth with the production of low-specific gravity wood to greater structural reinforcement of the trunk (production of denser wood) in three tropical pioneer species (Hampea appendiculata, Heliocarpus appendiculatus, and Ochroma pyramidale) in Costa Rica.…”
Section: Discussionmentioning
confidence: 75%
“…The relationship between radial growth increments and the xylem maturation process based on radial variation patterns of single or several wood properties has been reported for several fast-growing tree species in dry [9], tropical [14], and subarctic climates [15] (Table 6). In these studies, wood properties became stable below the age of 10 years at the time of peak CAI and MAI values in L. tulipifera in Japan (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nowadays, eucalyptus plants are widely planted all over the world and many researchers have extensively studied eucalyptus cultivation widely [1][2][3][4][5][6]. Eucalyptus is cheap, easy to grow and has many uses, such as being extracted as a mosquito and insect repellent, the essential oils are used to relieve nasal congestion and the bark is finely ground used to make incense.…”
Section: Introductionmentioning
confidence: 99%